Phytochemical screening and antimicrobial activity of Katmon (Dillenia philippinensis) Fruit pilp and fruit peel extract. - Espinosa, Jacklyn Pearl (2014.)
This study primarily aimed to determine the phytochemical content and antimicrobial activity of Katmon (Dillenia philippinensis) fruit pulp and fruit peel extract against Candida albicans, Esherichia coli and Staphylococcus aureus., Results of the phytochemical screening indicated that Katmon (Dillenia philippinensis) fruit pulp and fruit peel contained flavanoids, as shown by the formation of intense yellow solution; terpenes, as indicated by the presence of reddish brown color in solution using the Liebermann-Burcharcd Test; alkaloids, as marked by a violet solution with brown precipitate in the Wagner's Test; steroids, as signified by yellow green color on the organic layer; tannins, as indicated by the formation of yellow precipitate and glycosides, manifested by the formation of brick red precipitate when the extract was subjected to Fehling's Test. The Kirby-Bauer Disk Diffusion Method showed that Katmon fruit pulp extract possessed a very strong antimicrobial activity against Escherichia coli and minimal on Staphylococcus aureus. However, the Katmon fruit pulp extract showed negative inhibitions activity against Candida albicans. Alternatively, the Katmon fruit peel exhibited a very strong antimicrobial activity against Staphylococcus aureus and minimal on Escherichia coli and Candida albicans. It was also found out that a significant difference existed between and among the zones of inhibition of the three test organisms subjected to Katmon fruit pulp and fruit peel.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Katmon -- Fruit; Dillenia Philippinensis